Afghan War Crimes Victims Still Awaiting Justice - Patricia Gossman (Human Rights Watch, 2025)
Family members of Afghans unlawfully killed by foreign military forces during the 20-year war in Afghanistan have been waiting a long time for justice. Last week revealed two quite different approaches by countries that should provide it.
United Kingdom